Des pratiques interculturelles dans les écoles des régions du Québec : un modèle à inventer ? - Michèle Vatz Laaroussi; Marilyn Steinbach (Recherches en Éducation)
While intercultural practices are well established in certain schools in Montreal where ethnic and cultural diversity has been in the picture for several years, it is different in regions of Quebec more recently exposed to this diversity in their populations. However, regionalisation policies of immigration, in place in Quebec since 1993, demand a more open intercultural capital in the regions than in the metropolitan centers. How are intercultural relations going in the school context in the regions of Quebec? What are the issues, the principal obstacles and the facilitating factors? These are the guiding questions of this article. Based on different research on collaboration between immigrant families and schools and on immigration to the regions of Quebec, this article reflects on facets of cultural diversity in the school context in regional areas and on the development of new spaces of interculturality.